Implementation of Physical Test Measurement Using PJOK Application in Handball Sports (JTIKOR (Jurnal Terapan Ilmu Keolahragaan), 2024)
The study aims to evaluate students' physical condition. This study is descriptive and was conducted on fifth grade students of Elementary School 112 Palembang. The purpose of this study was to determine the average results of students' physical condition measurements in handball sports using the application. The dominant physical components in handball include speed, agility, leg muscle explosive power, strength, and endurance. A total of 30 students were the subjects of this study, consisting of 11 male students and 19 female students. Measurements were carried out through a 30-meter running test, agility test using the agility T-test, leg muscle explosive power was measured using a vertical jump test, strength was tested using a sit-up test, and endurance was measured using a beep test. The data obtained were analyzed using quantitative descriptive techniques. The results of the study showed that the average physical condition of fifth grade students of SD Negeri 112 Palembang in the handball sport was in the "very good" category with a percentage of 40%, the "good" category 7%, the "sufficient" category 9%, the "less" category 14%, and the "very less" category 30%. The conclusion of this study shows that most students have very good physical conditions. It is hoped that students can maintain and improve their physical condition in order to achieve higher achievements in the future.